2016
DOI: 10.1108/ijoa-08-2015-0900
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organizational and job characteristics on employees’ organizational commitment in arts-and-culture organizations

Abstract: Purpose The purpose of this paper is to investigate the nature of organizational commitment among employees of Palestinian arts-and-culture organizations and to examine the combined effect and role of organizational and job characteristics in shaping employees’ commitment. Design/methodology/approach An on-site employee survey was conducted in 20 distinct local not-for-profit arts-and-culture organizations, where the respondent sampling frame constituted of 190 individuals with a response rate of 48 per cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Employees with high levels of affective commitment have a higher possibility of remaining in the organization due to their less intention to quit (Meyer and Allen, 1991). Furthermore, being the most notable factor of other behaviors (Lavelle et al, 2007), affective commitment provides a highly accurate explanation of organizational commitment (Sabella et al, 2016). More specifically, an affective commitment was found to positively influence job-related behaviors and attitudes, such as job satisfaction (Marcovitz et al, 2007) and organizational citizenship behavior (Liu, 2009).…”
Section: Leadership and Affective Commitmentmentioning
confidence: 99%
“…Employees with high levels of affective commitment have a higher possibility of remaining in the organization due to their less intention to quit (Meyer and Allen, 1991). Furthermore, being the most notable factor of other behaviors (Lavelle et al, 2007), affective commitment provides a highly accurate explanation of organizational commitment (Sabella et al, 2016). More specifically, an affective commitment was found to positively influence job-related behaviors and attitudes, such as job satisfaction (Marcovitz et al, 2007) and organizational citizenship behavior (Liu, 2009).…”
Section: Leadership and Affective Commitmentmentioning
confidence: 99%
“…If the principal feels that what he has done has benefited others, himself or his family, it will further encourage his enthusiasm to complete each of his work and will lead to a stronger commitment in carrying out each task. The results of previous studies conducted by Chang and Lee (2006), Ali (2015), Obi-Nwosu, Chiamaka and Tochukwu (2013), Sabella, El-Far and Eid (2016) also showed that job characteristics influence organizational commitment. Thus, these findings are consistent, support and confirm the results of previous studies that job characteristics has a positive and significant direct effect on organizational commitment with the setting of the principals of Private Vocational High Schools in DKI Jakarta Province, Indonesia.…”
Section: Direct Effect Job Characteristics On Organizational Commitmentmentioning
confidence: 73%
“…Organizational commitment is also influenced by job characteristics. Several studies conducted by Chang and Lee (2006), Ali (2015), Obi-Nwosu, Chiamaka and Tochukwu (2013), and Sabella, El-Far and Eid (2016) have shown that job characteristics influences organizational commitment. Thus, it can be hypothesized: H5: Job characteristics has a direct effect on organizational commitment.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…And the third factor is talking about the commitment of an individual to stay in an organization even extra effort is required. Several studies have also been defined that affective commitment is the most perfect to describe the positive behaviors of organizations related to others' commitment (Chen and Francesco, 2003;Lavelle et al,2007;Sabella et al, 2016). As explained above, it can be defined that affective commitment representation the overall organization commitment since a strong affective commitment bring employees to continue employment with the organization and tend to make more effort for the organization (Joo et al 2012).…”
Section: Affective Commitmentmentioning
confidence: 99%